Testicular Torsion in Patients With Intellectual and Developmental Disabilities - Lisa B. E. Shields MD; Michael W. Daniels MS; Dennis S. Peppas MD; Eran Rosenberg MD (SAGE Publishing, 2021)
Patients with intellectual/developmental disabilities are at risk of delayed diagnosis of testicular torsion due to their inability to effectively communicate their symptoms. We identified males ages 1 to 18 years with testicular torsion between January 1, 2015 and December 31, 2020, focusing on patients with intellectual and/or developmental disabilities. Of the 140 patients with testicular torsion, 5 (3.6%) patients exhibited intellectual/developmental disabilities with an inability to effectively verbalize testicular/groin/scrotal pain. The patients with intellectual/developmental disabilities underwent more orchiectomies (5/5, 100%, P  = .009) and had a longer duration of symptoms (median = 48 hours, P  = .047) compared to those without intellectual/developmental disabilities (51/135, 38% and median = 9 hours, respectively) (51/134, 38%) ( P  = .038). Parents and other caregivers of males with intellectual/developmental disabilities who are unable to adequately verbalize their testicular/groin/scrotal pain should be cognizant of the signs and symptoms associated with testicular torsion, perform a genitalia examination, and seek an immediate evaluation to diagnose and treat this urgent condition.